Screening Senyawa Pandu Inhibitor Endositosis dengan Metode Molecular Modelling - Dian Herlinda Octorina Howan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The purpose of this research is to search for compound inhibitor endocytosis by using Molecular Modeling program. Screening is performed on approximately 800,000 compounds derived from several commercial companies. From the results of virtual screening obtained 320 hits, and of this number only 175 compounds that can be obtained to test its biological activity. Biological tests showed that there were 7 compounds with moderate endocytosis inhibition capability (IC50 = 50-170 μM) to good inhibition (IC50 <50 μM). The compounds are: compound 1 (IC50 = 42 ± 4 μM), compound 2 (IC50 = 83 ± 8 μM), compound 3 (IC50 = 135 ± 58 μM), compound 4 (IC50 = 151 ± 18 μM) compound 5 (IC50 = 144 ± 18 μM), compound 6 (IC50 = 13 ± 4 μM), and compound 7 (IC50 170 μM).